2012
DOI: 10.5402/2012/563191
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Land Use System and Environmental Factors Affect Arbuscular Mycorrhizal Fungal Density and Diversity, and Enzyme Activities in Rhizospheric Soils of Acacia senegal (L.) Willd.

Abstract: The responses of the soil microbial community features associated to the legume tree Acacia senegal (L.) Willd. including both arbuscular mycorrhizal fungal (AMF) diversity and soil bacterial functions, were investigated under contrasting environmental conditions. Soil samples were collected during dry and rainy seasons in two contrasting rainfall sites of Senegal (Dahra and Goudiry, in arid and semiarid zone, resp.). Soils were taken from the rhizosphere of A. senegal both in plantation and natural stands in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
3
15
1
1
Order By: Relevance
“…These results confirmed the ability of the primer AML2 to amplify several groups of AMF and indicated a wide diversity of AMF in roots of cowpea (Lee et al, 2008). However, these findings were opposed to those of Manga et al (2007) and Ndoye et al (2012) who found only species of the genus Glomus in rhizosphere of Acacia senegal in the semi-arid zone of Bambey and Dahra (Senegal), respectively. Nevertheless, Ngonkeu (2009) using the same fungal primers as the previous authors (LR1, FLR4), had already found some Gigasporaceae and Acaulosporaceae species in the roots of corn in Cameroon.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These results confirmed the ability of the primer AML2 to amplify several groups of AMF and indicated a wide diversity of AMF in roots of cowpea (Lee et al, 2008). However, these findings were opposed to those of Manga et al (2007) and Ndoye et al (2012) who found only species of the genus Glomus in rhizosphere of Acacia senegal in the semi-arid zone of Bambey and Dahra (Senegal), respectively. Nevertheless, Ngonkeu (2009) using the same fungal primers as the previous authors (LR1, FLR4), had already found some Gigasporaceae and Acaulosporaceae species in the roots of corn in Cameroon.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, Ngonkeu (2009) using the same fungal primers as the previous authors (LR1, FLR4), had already found some Gigasporaceae and Acaulosporaceae species in the roots of corn in Cameroon. These results might be explained by a selective mycorrhization (Helgason et al, 2002) in acacia trees because other species of fungi were found in their root zone particularly in Acacia senegal (Ndoye et al, 2012). The genus Glomus is the most diverse in our study with six species, representing 40% of all the species found in roots of cowpea.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In a study with Acacia senegal in the sahelian regions of Senegal, Ndoye et al (2012) found that the positive effects of this plant species on AMF spore density and diversity as well as on soil microbial functions can be influenced by land-use systems (plantations versus natural populations of A. senegal). In tropical dry ecosystems of Mexico, Gavito et al (2008) found higher AMF morphospecies richness in primary forests than in secondary forests and pastures.…”
Section: Introductionmentioning
confidence: 99%